Exploring the Growth of Reflective Practice in Higher Education - Bakar, Mohamad Azhari Abu; Ghani, Kartini Abd; Hutasuhut, Ida Juliana; Saili, Jamayah (International Journal of Psychosocial Rehabilitation, 2020)
Reflective practice is a process to explore the mental states of oneself, and others which allow students to experience deep learning. This practice increases the active engagement of students and personal ownership of self-development. Active thinking is also required which involves attentional control and meta-cognition. This study aims to explore the growth of reflective practice among psychology undergraduate students. A total of twenty-five (25) first-year psychology students from a university in Malaysia participated in this study. Participants have to write reflective journals related to specific learning topics for 10 weeks. Each reflective writing received personalised feedback from the researcher based on the five levels of the reflective practice coding scheme. A total of 138 reflective practice documents were analysed and categorised from Category 0 (non-reflective) to Category 4 (Critical reflective practice). The frequency of the five levels, reflective practice responses, and measures of academic performance was collected. Findings from this study support previous research on the positive contribution of reflective practice. It addresses the efficacy of response frequency to scaffold academic performance. The improvement of reflective practice styles requires a high level of effort, active thinking, and working memory activation.